Banking soundness and systemic risk: Insights from the Egyptian banking sector - Barakat, Hanan Amin (International Journal of Innovative Research and Scientific Studies, 2025)
This study investigates the relationship between key banking soundness indicators—capital adequacy, asset quality, profitability, liquidity, and efficiency—and systemic risk within Egypt’s banking sector. The purpose is to identify the primary drivers of systemic risk and provide actionable insights to enhance financial stability in emerging economies. Using panel data from nine banks listed on the Egyptian Exchange between 2011 and 2021, the research employs Value-at-Risk (VaR) as the systemic risk measure. It applies the Generalized Method of Moments (GMM) approach to address dynamic interactions and mitigate endogeneity concerns. The findings reveal that capital adequacy, asset quality, and profitability have a significant influence on systemic risk, highlighting the importance of maintaining robust capital buffers, implementing effective credit risk management, and developing thoughtful profitability strategies. Conversely, liquidity and efficiency metrics were found to have no substantial impact on systemic risk in the Egyptian banking context. The study emphasizes the necessity of prioritizing the monitoring and regulation of capital adequacy and asset quality to mitigate systemic vulnerabilities and enhance the resilience of the financial system. Additionally, it contributes to the literature by offering valuable insights into the interactions between banking stability indicators and systemic risk in emerging markets, providing a strong foundation for future research. These findings have practical implications for both policymakers and banking executives. Policymakers are encouraged to refine macroprudential regulations to emphasize robust capital planning and credit risk oversight, ensuring systemic stability. Bank executives can use these insights to align profitability strategies with comprehensive risk management objectives. Overall, this study offers actionable recommendations aimed at fostering a sustainable and resilient banking sector in Egypt.